2015
DOI: 10.1097/ijg.0b013e31829d9b5c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dorzolamide/Timolol Versus Brimonidine/Timolol Fixed Combination Therapy in the Management of Steroid-Induced Ocular Hypertension

Abstract: Both FCBT and FCDT are effective in controlling IOP elevations after IVTA injections. The results of this study suggest that FCBT is superior to FCDT in reducing IOP and provides better IOP control after IVTA injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Their conclusion was that the safety and daytime efficacy of these two FCs were comparable when employed in patients with OAG or OHT. However, in patients with steroid glaucoma BmTFC may obtain a greater hypotensive effect than DTFC [90]. This finding suggests that the effect on the trabecular meshwork of topically applied adrenergic agents may be beneficial in steroid glaucoma.…”
Section: Dtfc Therapy Employed In the Real Worldmentioning
confidence: 93%
“…Their conclusion was that the safety and daytime efficacy of these two FCs were comparable when employed in patients with OAG or OHT. However, in patients with steroid glaucoma BmTFC may obtain a greater hypotensive effect than DTFC [90]. This finding suggests that the effect on the trabecular meshwork of topically applied adrenergic agents may be beneficial in steroid glaucoma.…”
Section: Dtfc Therapy Employed In the Real Worldmentioning
confidence: 93%
“…Multiple clinical trials reported that BrT-FC is better than DzT-FC in reducing IOP, although no statistically significant difference is found ( Gulkilik et al, 2011 ; Feke et al, 2013 ; Seymenoglu et al, 2015 ). The side-effect profile of BrT-FC is similar to that of DzT-FC.…”
Section: Topical Fixed Combination Of Two Agentsmentioning
confidence: 94%
“…6 Brimonidine/timolol fixed-combination (BTFC) therapy has been established as an effective IOP-lowering treatment option for glaucoma, and a recent study reported an approximately two-fold higher IOP-lowering effect was achieved with this medication as compared with 0.5% timolol in normal-tension glaucoma patients. [7][8][9] However, much like generally used glaucoma ophthalmic solutions, BTFC ophthalmic solutions also contain benzalkonium chloride (BAK) as a preservative, which may cause ocular side effects such as mucous cell death, tear film instability, and lacrimation, especially in long-term users. 10 Many researchers have recently sought to further elucidate the harmful effect of preservatives, and the European Glaucoma Society now recommends preservative-free (PF) products for use by patients who have severe dry eye or ocular surface diseases.…”
Section: Introductionmentioning
confidence: 99%